Understanding academic burnout: the impact of social support and self-efficacy on final-year management students in Banjarmasin - Maryanti, Annisa; Nastiti, Rizky; Bachtiar, Yanuar; Daud, Ibrahim (Enrichment : Journal of Management, 2025)
Academic burnout is a critical issue affecting student well-being and academic performance, particularly among final-year university students engaged in thesis completion. Social support and self-efficacy are recognized as important psychological factors that can reduce stress, foster resilience, and improve students’ ability to cope with academic demands. This study investigates the effects of social support and self-efficacy on academic burnout among final-year management students in Banjarmasin. The study involved a sample of 100 students selected through proportional stratified random sampling, and the data were analyzed using multiple linear regression to examine the relationships between these variables. The findings reveal that social support has a positive but not significant effect on academic burnout, while self-efficacy shows a negative and significant effect, indicating its crucial role in mitigating burnout. Moreover, the combined influence of social support and self-efficacy is significant in reducing academic burnout. These results suggest that strengthening students’ self-efficacy and fostering supportive academic and social environments can help reduce burnout and enhance student resilience during thesis completion. The insights of this study provide valuable implications for higher education institutions in developing interventions and support systems that address the psychological needs of students in their final academic phase